TRENDS IN THE DEVELOPMENT OF INTEGRATED STEAM DIGITAL LEARNING MEDIA IN PRIMARY SCHOOLS FROM 2020 TO 2025 - Karin Widya Ayuningtyas; Arif Widiyatmoko; Bambang Subali; Nuni Widiarti (Universitas Majalengka, 2026)
The rapid advancement of digital technology requires the education sector to continually innovate in designing interactive, contextual, and relevant learning that aligns with 21st-century demands. One approach that has received increasing attention is STEAM-integrated digital learning, which combines Science, Technology, Engineering, Arts, and Mathematics. This approach is believed to enhance higher-order thinking skills, particularly critical thinking, while also strengthening creativity, collaboration, and communication (4C) among primary school students. This study aims to systematically review research trends on the development and implementation of STEAM-integrated digital learning media in primary schools from 2020 to 2025. Employing a Systematic Literature Review guided by PRISMA 2020, data were collected from five major databases: Google Scholar, Scopus, ERIC, ScienceDirect, and DOAJ. Through a structured selection process, 20 relevant journal articles published within the specified period were analyzed using basic bibliometric and thematic analysis techniques. The findings reveal a notable increase in publications in 2022. Dominant keywords include STEAM, Augmented Reality, Critical Thinking, and Elementary School. The most frequently examined learning media were Augmented Reality and interactive or mobile learning applications, commonly implemented through Project-Based Learning and Problem-Based Learning models. Most studies (85%) primarily focused on critical thinking, with creativity and cognitive learning outcomes also receiving considerable attention. Research and Development (60%) and quasi-experimental methods (30%) were the most commonly employed research designs. Overall, the integration of digital technology in STEAM learning demonstrates positive effects on the development of primary school students’ 4C competencies; however, this review contributes novel insights by systematically mapping the limited exploration of collaboration and communication skills within STEAM-based digital learning research at the primary education level.